Sintered high-zirconium brick and preparation method thereof

By using sintered high-zirconium bricks at the liquid surface line position of the melting pool of the glass kiln, combined with reasonable preparation and high-temperature sintering technology, the problem of insufficient corrosion resistance of the existing bricks at the liquid surface line position is solved, which significantly improves the resistance to glass corrosion and thermal shock resistance, extends the service life of the kiln and reduces maintenance costs.

CN116986897BActive Publication Date: 2025-04-11ZHENGZHOU FANGMING HIGH TEMPERATURE CERAMIC NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310924105.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-04-11
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

The existing glass kiln melting pool wall bricks have insufficient corrosion resistance at the liquid level line position, resulting in hollows in the brick structure, penetration and erosion of high-temperature glass liquid, shortening the service life of the kiln and increasing maintenance costs.

Method used

Sintered high-zirconium bricks are used to reasonably prepare components such as ZrO2, ZA eutectics, rare earth oxides, etc., and vacuum high-pressure molding and high-temperature sintering processes are adopted to ensure the zero-glass phase content of the product and improve the resistance to glass corrosion and thermal shock.

Benefits of technology

It significantly improves the glass corrosion resistance and service life of the bricks at the liquid surface line of the melting pool of the glass kiln, reduces the furnace maintenance cost, and has excellent cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116986897B_ABST
    Figure CN116986897B_ABST
Patent Text Reader

Abstract

The present invention relates to a sintered high-zirconium brick and a preparation method thereof. The sintered high-zirconium brick used for the liquid surface line position of a glass melting pool is made of the following raw materials in weight percentage: ZrO276-88wt%; ZA eutectic 5-10wt%; Y2O32-8wt%; MgO 2-6wt%; CaO 2-4wt%; CeO20.4-1.2wt%; SrO0.3-1wt%. The sintered high-zirconium brick of the present invention introduces zirconium dioxide, a main component that resists glass erosion, and the product is sintered at high temperature for a long time, so that the crystal is well developed. The sintered high-zirconium brick of the present invention introduces corundum baddeleyite plate-like eutectic into the system ingredients. This eutectic belongs to a plate-like structure and has the performance of buffering thermal stress, so that the product has excellent thermal shock resistance. The sintered high-zirconium brick of the present invention has excellent glass erosion resistance and an ideal service life, which is of great significance for glass enterprises to improve product quality, reduce costs, and improve corporate and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-temperature inorganic new materials, and in particular relates to high-zirconium bricks sintered at the liquid level position of a glass melting pool and a preparation method thereof. Background Art

[0002] At present, the melting pool wall of domestic glass kiln adopts fused zirconium corundum bricks (abbreviated as fused AZS). According to the zirconium dioxide content contained in the fused zirconium corundum bricks, there are AZS33#, AZS36#, and AZS41#, representing ZrO2 content of 33%, 36%, and 41% respectively.

[0003] Fused zirconium corundum pool wall bricks are made of industrial alumina and zircon sand (containing about 65% ZrO2 and about 34% SiO2), plus some soda ash Na2CO3, melted and cast in an electric arc furnace. The physical phase composition of the brick is: corundum, baddeleyite, corundum baddeleyite eutectic, and glass phase. Because there is about 15% low-melting point glass phase in the brick, the glass phase in the brick continuously precipitates on the surface of the brick under high-temperature working conditions, and is continuously physically washed with the flowing high-temperature glass liquid, causing cavities in the internal structure of the brick body, and then the high-temperature glass liquid gradually penetrates and erodes along the surface of the brick body. After the penetration layer gradually becomes a metamorphic layer, it falls off and is lost in the glass liquid. Under the dual effects of physical scouring and chemical erosion of the glass liquid on the bricks, the thickness of the pool wall bricks continues to decrease. When the thickness of the pool wall bricks is reduced to 60-80mm, the outer wall of the melting pool has to increase the brick tying or stop the furnace for maintenance, which will cause maintenance or production suspension losses and increase the production costs of glass companies.

[0004] At present, according to the conventional design of the liquid level line of the melting pool of the domestic glass furnace, the liquid level line position is set at a position 50mm downward from the top of the pool wall brick, see attached Figure 2 . By observing the erosion of fused AZS pool wall tiles, it was found that the most severely eroded parts of the pool wall tiles were at the liquid level line of the glass melting pool. The erosion depth of the same AZS pool wall tile at the liquid level line was 3-5 times that of other parts. The reason is that the liquid level line of the glass melting pool is the junction of solid, liquid and gas, and the glass material liquid has a high temperature and fast flow rate, which leads to the erosion rate of fused AZS bricks at the liquid level line position far exceeding other parts of the fused AZS bricks. Therefore, it is of great significance to optimize and improve the anti-erosion performance of the pool wall tiles at the liquid level line of the glass melting pool, increase the life of the kiln, and reduce the maintenance cost of the kiln. Summary of the invention

[0005] The object of the present invention is to overcome the deficiencies in the prior art and to provide a sintered high-zirconium brick for the liquid level position of a glass melting pool and a preparation method thereof.

[0006] The technical ideas of the present invention to solve the above technical problems are as follows: improve the corrosion resistance of the liquid level line of the wall bricks of the glass kiln melting pool from the following aspects: first, ensure that the content of the ZrO2 component is within a reasonable range; second, add corundum and zircon plate eutectic (ZA eutectic for short) to further optimize the thermal shock resistance of the product under the premise of meeting the corrosion resistance of the product; third, add rare earth oxide components with high melting points that inhibit glass liquid corrosion; fourth, ensure to the maximum extent that the goal of zero glass phase content of the product is achieved; fifth, adopt a special manufacturing process of vacuum high-pressure molding and high-temperature sintering. Therefore, the use of sintered high-zirconium bricks at the liquid level line of the glass kiln melting pool will not significantly increase the construction cost of the glass kiln, but can significantly improve the overall service life of the glass kiln, and has excellent cost performance.

[0007] The present invention is achieved through the following technical scheme: a sintered high-zirconium brick used for the liquid surface line position of a glass melting pool is made of the following raw materials in weight percentage: ZrO2 76-88wt%; ZA eutectic 5-10wt%; Y2O3 2-8wt%; MgO 2-6wt%; CaO 2-4wt%; CeO2 0.4-1.2wt%; SrO 0.3-1wt%.

[0008] Furthermore, the purity of the ZrO2 is not less than 99%, and the particle size is 1um-30um.

[0009] Furthermore, the contents of ZrO2 and Al2O3 in the ZA eutectic are not less than 99%, and the particle size is 2um-44um.

[0010] Furthermore, the purity of the Y2O3 is not less than 99%, and the particle size is 1um-10um.

[0011] Furthermore, the purity of the MgO is not less than 99%, and the particle size is 2um-10um.

[0012] Furthermore, the CaO purity is not less than 99% and the particle size is 2um-10um.

[0013] Furthermore, the purity of the CeO2 is not less than 99%, and the particle size is 0.2um-8um.

[0014] Furthermore, the purity of the SrO is not less than 99%, and the particle size is 0.2um-8um.

[0015] A method for preparing a sintered high-zirconium brick for a glass melting pool liquid level position comprises the following steps:

[0016] Step 1, material mixing and granulation, according to the above raw material types and proportions, the raw materials are put into a three-dimensional mixer and mixed for 24 hours; the mixed raw materials are then put into a granulator for granulation and screening, and the granulation particle size is controlled to be 20-180 mesh to obtain a blank.

[0017] Step 2: forming and blanking. The granulated raw materials are put into the mold cavity of a high-tonnage vacuum press for pressure forming. The absolute value of the vacuum degree is not less than 0.09MPa, and the forming pressure is not less than 800MPa to obtain a dense semi-finished blank.

[0018] Step three, firing, raising the temperature to 1700-1750°C, sintering at a constant temperature for 25-36 hours, and obtaining sintered high-zirconium bricks for the liquid level position of the glass melting pool after cooling.

[0019] The beneficial effects of the present invention are as follows: the sintered high-zirconium bricks used at the liquid level of the glass melting pool are resistant to glass erosion and have a long service life. The main mechanism is:

[0020] 1. The sintered high-zirconium brick of the present application introduces 76-88wt% zirconium dioxide, the main component for resisting glass corrosion, and the crystals are well developed due to the long-term high-temperature sintering of the product. If the ZrO2 component content is less than 76%, the corrosion resistance of the product will be attenuated; if the ZrO2 component content is greater than 88%, the corrosion resistance will not be significantly improved, but the thermal shock resistance of the product will be deteriorated.

[0021] 2. The sintered high-zirconium bricks of the present application have introduced corundum-badge zircon plate-like eutectics into the system ingredients. This eutectic has a plate-like structure and has the ability to buffer thermal stress, so that the product has excellent thermal shock resistance.

[0022] 3. The sintered high-zirconium bricks of the present application introduce high-melting-point, corrosion-resistant components - rare earth oxides cerium oxide CeO2 and strontium oxide SrO into the system ingredients. CeO2 has the function of further stabilizing the ZrO2 lattice, so that the zirconium oxide in the product does not produce volume changes during phase change due to temperature changes; SrO can effectively prevent SiO2 in the glass liquid from reacting with stabilizers (MgO, CaO) in the zirconium oxide lattice, and has the function of preventing zirconium oxide from destabilizing. The introduction of rare earth raw materials further optimizes the corrosion resistance and thermal shock resistance of the product.

[0023] 4. The three oxide components Y2O3, MgO and CaO introduced into the sintered high zirconium brick of the present application are composite stabilizers of zirconium oxide. Since the ionic radius of these three oxide components is similar to that of zirconium oxide, they can form a solid solution with zirconium oxide, causing zirconium oxide to become a stable tetragonal or cubic phase, thus avoiding product cracking defects caused by volume expansion and contraction stress generated by phase change of zirconium oxide.

[0024] 5. The sintered high-zirconium bricks of the present application do not contain silicon dioxide and sodium oxide in the system ingredients, so that the harmful glass phase in the product is almost zero.

[0025] 6. The sintered high-zirconium bricks of the present application adopt a high-tonnage vacuum press for pressurization in the molding process and a long-term high-temperature sintering process, so that the products have high density, low porosity, and excellent structural properties, making it difficult for the glass liquid to cause penetration erosion to the products.

[0026] Therefore, the sintered high-zirconium bricks of the present application have excellent glass erosion resistance and ideal service life, which is of great significance for glass companies to improve product quality, reduce costs, and improve corporate and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 One is a comparison diagram of the samples of the sintered high zirconium brick prepared in Example 2 of the present application and the AZS brick 33# after being eroded and cut along the center line.

[0028] Figure 2 This is a comparison chart of the sintered high-zirconium bricks and AZS brick 33# prepared in Example 2 of the present application before and after dynamic anti-erosion samples. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of the embodiments. Based on the embodiments of the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.

[0030] In the following embodiments,

[0031] The purity of ZrO2 is not less than 99% and the particle size is 1um-30um.

[0032] The contents of ZrO2 and AI2O3 in the ZA eutectic are not less than 99%, and the particle size is 2um-44um.

[0033] The purity of Y2O3 is not less than 99% and the particle size is 1um-10um.

[0034] The purity of MgO is not less than 99% and the particle size is 2um-10um.

[0035] The purity of CaO is not less than 99% and the particle size is 2um-10um.

[0036] The purity of CeO2 is not less than 99% and the particle size is 0.2um-8um.

[0037] The purity of SrO is not less than 99% and the particle size is 0.2um-8um.

[0038] The preparation method of the sintered high-zirconium brick used for the liquid level position of the glass melting pool comprises the following steps:

[0039] Step 1, material mixing and granulation, according to the raw material ratio, the relevant raw materials are put into a three-dimensional mixer and mixed for 24 hours; the mixed raw materials are then put into a granulator for granulation and screening, and the granulation particle size is controlled to be 20-180 mesh to obtain a blank.

[0040] Step 2: forming and blanking. The granulated raw materials are put into the mold cavity of a high-tonnage vacuum press for pressure forming. The absolute value of the vacuum degree is not less than 0.09MPa, and the forming pressure is not less than 800MPa to obtain a semi-finished blank.

[0041] Step 3: sintering: heating to 1680-1750℃, sintering at a constant temperature for 20-26h, and cooling to obtain sintered high-zirconium bricks for the liquid level position of the glass melting pool.

[0042] Example 1

[0043] A sintered high-zirconium brick used for the liquid level position of a glass melting pool, comprising the following raw materials by mass percentage

[0044] Zirconium dioxide material: 88%;

[0045] ZA eutectic material: 6%

[0046] Yttrium oxide material: 2%;

[0047] Magnesium oxide material: 2%;

[0048] Calcium oxide material: 1%;

[0049] Cerium oxide material: 0.6%;

[0050] Strontium oxide material: 0.4%

[0051] Example 2

[0052] A sintered high-zirconium brick used for the liquid level position of a glass melting pool, comprising the following raw materials by mass percentage

[0053] Zirconium dioxide material: 83%;

[0054] ZA eutectic material: 7%

[0055] Yttrium oxide material: 5%;

[0056] Magnesium oxide material: 2%;

[0057] Calcium oxide material: 2%;

[0058] Cerium oxide material: 0.7%;

[0059] Strontium oxide material: 0.3%

[0060] Example 3

[0061] A sintered high-zirconium brick used for the liquid level position of a glass melting pool, comprising the following raw materials by mass percentage

[0062] Zirconium dioxide material: 76%;

[0063] ZA eutectic material: 10%

[0064] Yttrium oxide material: 4%;

[0065] Magnesium oxide material: 4.5%;

[0066] Calcium oxide material: 4%;

[0067] Cerium oxide material: 0.8%;

[0068] Strontium oxide material: 0.7%

[0069] Performance parameter characterization:

[0070] 1. The relevant properties of the above-mentioned embodiments 1-3 and the comparative example AZS33# brick were tested, and the test standards involved are as follows:

[0071] The load softening temperature test is carried out in accordance with GB / T5989-1998;

[0072] The apparent porosity test is carried out in accordance with GB / T2997-2000;

[0073] The bulk density test is carried out in accordance with GB / T2997-2000;

[0074] The compressive strength test is carried out in accordance with GB / T50081-2002;

[0075] The thermal shock stability test is carried out in accordance with the standard YB / T376.1-1995.

[0076] The relevant performance test results are as follows:

[0077]

[0078] It can be seen from the above table that the various performance indicators of the sintered high-zirconium bricks invented in this application are better than 33# fused AZS bricks.

[0079] 2. Anti-glass liquid corrosion test

[0080] The sintered high-zirconium brick prepared in Example 2 of the present application and the 33# fused AZS brick were subjected to a comparative test on the erosion resistance of molten glass. The comparative test conditions were as follows:

[0081] Corrosive media High silicate glass Test temperature 1600℃ Insulation time 48h Sample speed 50 rpm

[0082] The comparative test results are as follows:

[0083]

[0084] From the test data of the anti-glass liquid corrosion test and the pictures of the samples after corrosion described in the above table, it can be seen that the sintered high-zirconium bricks of the present invention have excellent anti-glass liquid corrosion performance. At the glass liquid surface line, the corrosion amount and corrosion rate index of the high-zirconium bricks are only 1.7% of that of the 33# fused AZS bricks, which is of great significance to greatly improve the life of the glass kiln and reduce the maintenance cost of the kiln.

[0085] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing sintered high zirconium bricks, characterized in that: The sintered high-zirconium brick is composed of the following raw materials: ZrO2 76-88wt%, ZA eutectic 5-10wt%, Y2O3 2-8wt%, MgO 2-6wt%, CaO 2-4wt%, CeO2 0.4-1.2wt%, SrO0.3-1wt%; the ZA eutectic is a corundum baddeleyite plate-like eutectic; The method comprises the following steps: Step 1, material mixing and granulation, according to the raw material ratio, the raw materials are put into a three-dimensional mixer and mixed for 24 hours; the mixed raw materials are then put into a granulator for granulation and screening, and the granulation particle size is controlled to be 20-180 mesh to obtain a blank; Step 2: forming and blanking, putting the granulated raw materials into the mold cavity of a high-tonnage vacuum press for pressure forming to obtain a dense semi-finished blank; Step three, sintering, raising the temperature to 1700-1750°C, sintering at a constant temperature for 25-36 hours, and obtaining sintered high-zirconium bricks after cooling.

2. A method for preparing sintered high zirconium bricks according to claim 1, characterized in that: The absolute value of the vacuum degree in step 2 is not less than 0.09 MPa.

3. A method for preparing sintered high zirconium bricks according to claim 1, characterized in that: The molding pressure in step 2 is not less than 800 MPa.

4. The sintered high-zirconium brick prepared by the method according to any one of claims 1 to 3, characterized in that: The weight percentage content of the raw materials is: 83wt% of zirconium oxide, 7wt% of ZA eutectic, 5wt% of Y2O3, 2wt% of MgO, 2wt% of CaO, 0.7wt% of CeO2, and 0.3wt% of SrO.

5. The sintered high-zirconium brick prepared by the method according to any one of claims 1 to 3, characterized in that: The contents of ZrO2 and Al2O3 in the ZA eutectic are not less than 99%, and the particle size is 2um-44um.

6. The sintered high-zirconium brick prepared by the method according to any one of claims 1 to 3, characterized in that: The purity of the ZrO2 is not less than 99%, and the particle size is 1um-30um.

7. Application of the sintered high-zirconium bricks described in any one of claims 4 to 6 at the liquid level of a glass melting pool.

Citation Information

Patent Citations

  • Gradient composite technology ceramic tile and preparation method thereof in field of glass kilns

    CN112225558A

  • Zirconia ceramic, preparation method thereof and ceramic filter

    CN112759387A